Fuelwood, Fodder and Livestock Status in a Himalayan Watershed in Mussoorie Hills (Uttarakhand, India) - Chandra, Ram; Soni, Prafulla; Yadav, Vinay (Indian Forester, 2008)
In the hill areas, the traditional systems of dependence on forest usufructs like fuel for their households and fodder for their livestock has an important bearing on the status of Himalayan watersheds. The population of livestock is therefore also significant. The fuel and fodder requirements of the hill people are important routine activities for which women/ children spend long hours of their day-to-day life. But this regular collection of the fuel and fodder from the different land use categories in close proximity of villages. These activities have been an important factor for causing soil erosion, low fertility of the land and other degradation processes. The situation is further aggravated if animals are not stall-fed but are allowed to graze. To assess these scenarios, a comparative study of the ten villages in Arnigad Watershed, Mussoorie (Uttarakhand) has been done. The results of this study provide a macro view of the societal dependence on the different land use categories in the watershed with reference to fuel, fodder consumption and livestock scenario in the individual villages as well as the watershed.